Linear random boundary value problems containing weakly correlated forcing functions - Ning-Mao Xia (International Journal of Mathematics and Mathematical Sciences)
This paper concerns linear random boundary value problems that contain random variables In the boundary conditions and weakly correlated processes in the differential equations. When the correlation length ϵ is small the structure of the solution is pointed out, and the formulas for the density function of the solutions are derived. The discussion is given in terms of second order equations, but extensions to higher order problems are readily apparent.